You've got the job [ legal rights and responsibilities of employees and employers - Garner, Simon , 1959-; Harding, Ben; Trikojus, Tom (Video Education Austaralasia, 2003)
This program looks at legal issues relating to employment for young people. It examines an employer's duties and responsibilities and is a useful guide for young people those already employed in part-time or casual work and those about to enter the workforce. The program also considers the rights and responsibilities of the employee